Entrepreneurship with Social Responsibility as an Innovative Tool for Solving Social Needs - Antonina Tomashevska; Iryna Hryhoruk (Vasyl Stefanyk Precarpathian National University, 2022)
The article deals with a historical retrospective of the emergence of social entrepreneurship. Approaches to the definition of the concept of "social entrepreneurship" are given and characterized. They are broad, combined, and problem-oriented. According to a study by The Possibilists, today businessmen from 138 countries are not motivated to start a business for their own needs and desires, they are motivated by the goal of improving the lives of others globally and locally. This is a huge paradigm shift in the cause of business that the world is living in right now. This change can be accelerated by crisis factors, which, unfortunately, occur in society. The article also analyzes the impact of the war in Ukraine on the development of social entrepreneurship. Often in our country, social entrepreneurship exists as a volunteer or charitable organization that has limited resources. Sometimes they are created in combination with business approaches and give a more sustainable effect. The legalization of the term "social entrepreneurship" has been analyzed. In Ukraine, there are false statements about it that need to be clarified. The authors' definition of the essence of the category "social entrepreneurship" is presented. The main activities of social enterprises are listed and examples are given. The key differences between social entrepreneurship, charity, and traditional business are revealed. The characteristics of organizations engaged in social entrepreneurship are given. Current trends in the development of foreign social entrepreneurship are identified. The dynamics of the number of social enterprises in Ukraine are analyzed and the main organizational and legal forms of functioning of social enterprises in Ukraine are presented. The current problems and obstacles in social entrepreneurship are given, and the directions promoting the development of social business are defined.